GLYCYRHYRZIN ACID COMPLEXES IN COTTON UNDER SALINITY CONDITIONS (Gossypium barbadense L.) INFLUENCE ON SEED FERTILITY - Kushiev H.H; Djuraev T.A; Ismailjonova O.B. (Western European Studies, 2024)
Glycyrrhizin acid (GA): Supramolecular complexes of phytohormones (PH) (PH: indole-3-acetic acid (IAA); indole-3-butyric acid (IBA); naphthalene-1- acetic acid (NAA) and kinetin) (100 μM ) of cotton in laboratory conditions « Sultan » It was found that the intensity and amount of water-soaking dynamics of the variety seeds were significantly increased compared to the control, and the germination energy and germination level of the seeds were optimized under experimental salinity conditions (NaCl=200 mM). The obtained results show the high prospects of using supramolecular complexes of GA: phytohormones in agricultural practice to optimize the process of germination and development of plants under conditions of stress factors, including salinity.
Keywords: Glycyrrhizic acid; phytohormones; supramolecular complexe